EVALUATION OF BCG VACCINE COVERAGE IN THE MIDWEST REGION UNDER THE INFLUENCE OF THE PANDEMIC AND ANTI-VACCINE MOVEMENTS - Rangel, Thalysson de Souza; Pereira, Vitor Ramos Dayrell; Matos, Helena Diniz; Fleury , Rodrigo Augusto Mastrella Curado; Carvalho, Karla Cristina Naves (CIPEEX, 2025)
Vaccination is an important disease prevention measure, considered one of the greatest achievements in public health in the 20th century. Through the National Immunization Program, the Ministry of Health made vaccination mandatory in 1976 for the prevention of tuberculosis. The vaccine, called Bacillus Calmette-Guérin (BCG), requires only one dose, taken shortly after birth. The decline in vaccine adherence has been a source of great concern for Brazilian health authorities. Vaccine hesitancy, which involves apprehension about or refusal of vaccines, can lead to the creation of anti-vaccine movements, reducing access to this means of protection. Thus, the objective of this study is to identify the prevalence of BCG vaccination coverage in children and analyze the impact of the pandemic and anti-vaccine movements on BCG vaccination coverage in children in the pre-pandemic and post-pandemic periods. This study was conducted using data from 2018 to 2021, available on the DATASUS platform. The results show that BCG vaccination coverage in the Midwest region decreased in the 2020-2021 biennium compared to 2018 and 2019 in most of the states analyzed. This decrease occurred not only in this region but was observed throughout the country. It was concluded that there was a decrease in vaccination coverage in the Midwest region, with a need for normalization of services and causal investigations so that coverage levels return to the recommended target.